Cricoid pressure: The case in favour. Issue 2 (June 2015) - Athanassoglou, Vassilis; Pandit, Jaideep J.
Summary: Cricoid pressure (CP) was introduced into anaesthetic practice in the 1960s and has become the standard of care for patients at risk of aspiration during induction. However, the evidence supporting the widespread use of CP to prevent aspiration remains unconvincing. Equally, there is no robust evidence to suggest that CP causes harm, and as such, CP has become an established technique because of a mixture of anecdotal evidence and expert opinion. The future of CP lies in the answer to the question as to whether it is actually effective in preventing regurgitation or whether it is an unnecessary hazard.